2015
DOI: 10.1159/000371545
|View full text |Cite
|
Sign up to set email alerts
|

Serum Anti-60S Ribosomal Protein L29 Antibody as a Novel Prognostic Marker for Unresectable Pancreatic Cancer

Abstract: Background/Aims: Recently, we found the presence of anti-60S ribosomal protein L29 antibody (anti-RPL29) in human sera, inhibiting the proliferation of pancreatic cancer cells in vitro. We aimed to estimate the association of serum anti-RPL29 levels with clinical features in patients affected with unresectable pancreatic cancer. Methods: We retrospectively reviewed 105 patients with unresectable pancreatic cancer. Serum anti-RPL29 levels were measured by the indirect enzyme-linked immunosorbent assay. The cut-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Based upon title/abstract reading 1341 articles were not relevant to the topic leading to the full text screening of 41 articles. Ten of these were excluded due to the following reasons (see also Supplementary File S1 ): three studies evaluated markers other than autoantibodies or diagnostic ones [ 10 12 ], two studies lacked cancer free controls [ 13 , 14 ], we were unable to calculate sensitivity and specificity in four studies [ 15 18 ] and one study did not provide the number of included controls [ 19 ] In the end, with four articles additionally identified through cross-referencing [ 20 23 ], 31 articles were included in our review [ 20 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based upon title/abstract reading 1341 articles were not relevant to the topic leading to the full text screening of 41 articles. Ten of these were excluded due to the following reasons (see also Supplementary File S1 ): three studies evaluated markers other than autoantibodies or diagnostic ones [ 10 12 ], two studies lacked cancer free controls [ 13 , 14 ], we were unable to calculate sensitivity and specificity in four studies [ 15 18 ] and one study did not provide the number of included controls [ 19 ] In the end, with four articles additionally identified through cross-referencing [ 20 23 ], 31 articles were included in our review [ 20 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Zhao, et al., uncovered that AHSG is up-regulated in esophageal squamous cell carcinoma, and might also act as a pro-tumorigenic protein ( 37 ). By contrast, lower expression of RPL29, the one belongs to the NDP, is predicted to have a poorer outcome of unresectable pancreatic cancer ( 38 ), providing further evidence that RPL29 might be anti-tumorigenic. In liver cancer cells, we have revealed that NUPs are more likely to be predominantly expressed than NDPs, because NUPs are less ubiquitinated than regulated by NMT1.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a variant correlating with GWG in RPL29P25 gene. The presence of anti-60S ribosomal protein L29 (RPL29) antibody in human serum was shown to inhibit the proliferation of pancreatic cancer cells in various cancers and it is believed to be a novel candidate for a prognostic marker for unresectable pancreatic cancer (Muro, Miyake, Kato, Tsutsumi, & Yamamoto, 2015). The knockdown of RPL29 leads to suppression of cell proliferation, induces cell arrest (at G0/G1phase), enhances cell apoptosis and decreases intracellular ROS generation (C. Li, Ge, Yin, Luo, & Chen, 2012).…”
Section: Discussionmentioning
confidence: 99%